1980
DOI: 10.1007/bf00122407
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomes and types of parthenogenesis in the false spider mites (Acari: Tenuipalpidae)

Abstract: The chromosome numbers and types of parthenogenesis have been assessed for 19 species of 6 different genera of the Tenuipalpidae. The modal number of n = 2 is found to occur in species of the genera Aegyptobia, Cenopalpus, Brevipalpus, Dolichotetranychus and Raoiella. The bisexual species examined exhibit haplo-diploidy (with n = 2 and 2n = 4) as a result of arrhenotokous parthenogenesis. Thelytokous parthenogenesis with female diploidy is found in Aegyptobia vannus (2n = 4), Aegyptobia thujae (2n = 4) and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
15

Year Published

1984
1984
2009
2009

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 5 publications
1
13
0
15
Order By: Relevance
“…This high sex ratio was expected because B. phoenicis reproduces mainly by thelytokous parthenogenesis, in other words, non-fecundated females produce females identical to the progenitor (Haramoto, 1969;Helle et al, 1980), sexual repro- duction with the participation of males also exists, which is rare in the population. Fertility life table -The intrinsic rate of the population increase (r m ) was estimated at 0.128 females/female/day in citric fruit and 0.090 females/ female/day in coffee leaves ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This high sex ratio was expected because B. phoenicis reproduces mainly by thelytokous parthenogenesis, in other words, non-fecundated females produce females identical to the progenitor (Haramoto, 1969;Helle et al, 1980), sexual repro- duction with the participation of males also exists, which is rare in the population. Fertility life table -The intrinsic rate of the population increase (r m ) was estimated at 0.128 females/female/day in citric fruit and 0.090 females/ female/day in coffee leaves ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been frequently studied in insects (Suomalainen, 1962), but rarely in arachnids. Except for mites, where it is rather common (Helle et al, 1980), it is reported only for a few scorpions (Lourenço, 2002(Lourenço, , 2008, harvestmen (Tsurusaki, 1986), schizomids (Reddell & Cokendolpher, 1995) and amblypygids (Weygoldt, 2007), but there is little reliable information. Of the more than 40 000 species of spiders in the world (Platnick, 2008) only a few are parthenogenetic (Lake, 1986;Deeleman-Reinhold, 1986;Gruber, 1990;Shimojana & Nishihira, 2000;Edwards et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…O ácaro Brevipalpus se reproduz principalmente por partenogênese telítoca, isto é, fêmeas não fecundadas dão origem a fêmeas idênticas a progenitora (Helle et al, 1980), existindo também a reprodução sexuada, quando machos estão presentes na população (cerca de 1%). Estudos conduzidos por Weeks et al (2001) (Oliveira, 1986).…”
Section: Solanum Violaefolium Schott (Bitter)(= Lycianthes Asarifoliaunclassified